Recent advances in the treatment of premature ejaculation - Kate D Linton; Kevan R Wylie (Dove Medical Press, 2010)
Kate D Linton, Kevan R WylieSheffield Teaching Hospitals, Sheffield, UKAbstract: Premature ejaculation (PE) is the most common sexual problem affecting men. It can affect men at all ages and has a serious impact on the quality of life for men and their partners. Currently there are no pharmaceutical agents approved for use in the UK, and so all drugs used for this condition are off label. Behavioral therapy has been used to treat PE, but the results are not durable once therapy has been concluded. Several topical therapies have been used including severance-secret (SS) cream, lignocaine spray, lidocaine-prilocaine cream and lidocaine-prilocaine spray (TEMPE). There has been recent interest in the selective serotonin reuptake inhibitors (SSRIs) for the treatment of PE, due to the fact that one of their common side effects is delayed ejaculation. Currently used SSRIs have several non-sexual side effects and long half lives, therefore there has been interest in developing a short acting, efficacious SSRI that can be used on-demand for PE. Dapoxetine has been recently evaluated for the treatment of PE by several groups, and results so far appear promising.Keywords: premature ejaculation, topical therapies, selective serotonin re-uptake inhibitor, dapoxetine